WORKING STUDENTS AND THE CLOCK: HOW LEARNING MOTIVATION SHAPES ACADEMIC PROCRASTINATION - Rakha Pasha Rizaldi; Nur Ainy Sadijah; Yuwono Pratomo (EDUCATIONE, 2026)
This study aims to determine the influence of learning motivation and self-regulation on the academic procrastination of students working at X Karawang University. The population in this study of students working at Universitas X Karawang was 3,306 and the sample determination was 344 using the Issac and Michael formula with an error rate of 5%, the sampling used was a non-probability sampling method  by applying accidental sampling techniques. This study uses three psychological measurement tools: Academic Procrastination Scale (APS), Motivated Strategies for Learning Questionnaire (MSLQ), and Short Self-Regulation Questionnaire (SSRQ), this research method uses quantitative methods. Try-out, validity and realism test, data analysis using assumption tests, namely normality tests and linearity tests, and hypothesis tests, namely t-tests, f tests, multiple linear regression analysis and determination coefficients, data processing is carried out through  the Statistical Package for the Social Sciences (SPSS) application for Windows version 29.0. The results of multiple linear regression analysis suggest that the data is normally distributed (p = 0.095 > 0.05) and show a linear relationship between independent and dependent variables. The results of the hypothesis test revealed a significant negative influence of learning motivation on academic procrastination, Ha was accepted while H0 was rejected. The results of the second hypothesis test indicated that there was no effect of self-regulation on academic procrastination, so H0 was accepted. The results of the third hypothesis test, with a significance value of 0.002 (<0.05), indicate that learning motivation and self-regulation have a significant effect on academic procrastination, thus, the hypothesis is accepted.